Penerapan Metode Naïve Bayes Dalam Mendiagnosa Kerusakan Printer - Tiki Ramdhani; Toni Arifin (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
Printers are devices that are utilized as print media. Despite the fact that a lot of printers have issues, little is known about printer damage at this time. while damage necessitates careful handling. The Naive Bayes method is one of many methods that can be used in expert systems. The point of this examination is to figure out how to carry out the utilization of diagnosing printer harm utilizing the Guileless Bayes strategy at the TR PrintComp organization and to figure out what the test aftereffects of the application are in diagnosing printer harm utilizing the Gullible Bayes technique at the TR PrintComp organization. The exploration strategy involved is writing concentrate on in this examination bringing about an application for diagnosing harm to printers utilizing the Credulous Bayes technique. Black box testing and confusion matrix methods were used for testing. The consequences of this exploration show that scientists have prevailed with regards to making a specialist framework for diagnosing printer harm utilizing the Gullible Bayes technique utilizing the PHP and MySQL programming dialects as a data set. Based on expert system testing, the Naive Bayes method was used to accurately diagnose printer damage with a 72.4% success rate. It is anticipated that this expert system application will offer a different approach to dealing with printer damage issues. The result from this master framework is as data or data in regards to the sort of printer harm and is joined by arrangements and ways of defeating them. The author's implementation of the Naive Bayes method for diagnosing printer damage is able to quickly identify the kind of damage.